A Qualitative Study on the Dynamics of Social Solidarity in Overcoming Socio-Economic Crises and Challenges - Zaim Mukaffi; Amjad Hamad Abdullah (Jurnal Sosial Indonesia, 2026)
The intersection of populism, political interference, and bureaucratic neutrality has become a critical issue for democratic governance, particularly in the context of socio-economic crises. This study aims to explore how the rise of populist movements affects the politicization of bureaucracy and its implications for democratic integrity. Through a qualitative approach, the research examines the impact of populism on public institutions, focusing on the role of social solidarity in crisis management. By reviewing recent literature and empirical studies, the research identifies the tensions between political loyalty and bureaucratic impartiality, and how such pressures undermine the neutrality of public servants. The findings reveal that the politicization of bureaucracy leads to diminished public trust, decreased transparency, and weakened accountability in governance. In response, the study highlights the importance of safeguarding bureaucratic neutrality, particularly in times of populist political influence, to maintain the legitimacy of public institutions. Social solidarity emerges as a vital force in overcoming socio-economic challenges, fostering community resilience, and mitigating the adverse effects of crises. The research underscores the need for comprehensive reforms to protect bureaucratic institutions from political pressures and enhance social solidarity to ensure effective governance.